THE EFFECTS OF PAPAIN CRUDE EXTRACT ADDITION IN DIETS ON BROILERS PRODUCTION PERFORMANCES - Rumokoy, Laurentius; Pudjihastuti, Endang; Untu, Ivonne Maria; Toar, Wisje Lusia (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
This study was conducted to evaluate the effects of papain crude extract addition in mash and pellet feed forms on production performance of broiler chickens in order to obtain the best level of extract papain in mash or pellet form. This natural protease enzyme was extracted from unripe papaya. A complete random design was applied in this study and it was arranged with factorial 4 * 2 and three replications. The treatments were 4 levels of papain (0, 0.03, 0.05, and 0.07 %) and two physical forms of feed (mash and pellet). Broilers production parameters measured were: feed intake, body weight, feed conversion ratio (FCR) and carcass percentage. The results of analysis of variance showed that the interaction was highly significant (P <0.01) for feed intake, body weight, carcass percentage respectively while feed conversion showed significant interaction (P <0.05). The significant differences in the feed consumption described the role of papain enzyme through treatment of CEP and the physical form of feed. The results indicate that the all treatment of papain crude extract level both in mash and pellet feed form were able to improve feed intake, body weight, FCR and carcass percentage of broiler chickens, whereas the best performance was obtained in the treatment of 0.05% papain crude extract in mash form of diets.